Prevalence and risk factors of gross neurologic deficits in children after severe malaria: A systematic review and meta-analysis - Allen Eva Okullo; Simple Ouma; Chandy C. John; Michael Boele van Hensbroek; Kevin Ouma Ojiambo; Caroline Otike; Alison Annet Kinengyere; Andrea L. Conroy; Moses Ocan; Ekwaro A. Obuku; Richard Idro (PLoS ONE, 2026)
Background Children with severe malaria may develop gross neurologic deficit(s). We conducted a systematic review on the prevalence and risk factors of gross neurologic deficits after childhood severe malaria. Methods The systematic review was conducted following PRISMA guidelines. Article search was conducted in MEDLINE, EMBASE, Web of Science, and Global Index Medicus. Studies included reported on prevalence and/or risk factors of gross neurologic deficits after severe malaria in children. Risk of bias analysis and heterogeneity assessment were performed using ROBINS tool and I 2 -statistic, respectively. Data analysis was done using quantitative synthesis in R ver 4.5.0 software, and narrative synthesis. Results 41 studies from 16 countries in Sub-Saharan Africa and Asia comprising 11,635 children were included in the analysis. Gross neurologic deficits included motor, movement, sensory, and speech impairments. 31 studies included prevalence of gross neurologic deficits at hospital discharge (cerebral malaria (CM), n = 26, broader forms of severe malaria, n = 5). Prevalence of deficits at hospital discharge in children with CM was 15.2% (95%CI: 11.5–18.8) (I 2 = 89.1%), compared to 2.4% (95%CI: 2.0–2.8) (I 2 = 36.6%) in children with broader forms of severe malaria. Prevalence of deficits in CM decreased from 15.2% to 5.7% (95%CI: 1.2–10.2) (I 2 = 79.2%) after 12 months follow-up. At regional level, Sub-Saharan Africa had a prevalence of 14.2% (95%CI: 10.5–17.9) (I 2 = 94.9%) compared to East Asia & Pacific at 2.3% (95%CI: 0.8–3.8) (I 2 = 0.0%) and South Asia at 6.1% (95%CI: 0.0–14.8) (I 2 = 0.0%). Risk factors for gross neurologic deficits included profound coma, coma lasting ≥48 hours, multiple convulsions, hypoglycaemia, and acute kidney injury. Conclusions Gross neurologic deficits are more prevalent in children in Sub-Saharan Africa with CM compared to severe malaria in general, and a number of clinical factors in children with CM increase the risk. Interventions by clinicians should target children with CM at highest risk during admission.